Focus on ECT seizure quality: serum BDNF as a peripheral biomarker in depressed patients - Bumb, Jan Malte; Janke, Christoph; Gass, Peter; Sartorius, Alexander (European archives of psychiatry and clinical neuroscience, 2015)
Electroconvulsive therapy (ECT) is a well-established, safe and effective treatment in severest or drug-resistant affective disorders. The potential relation between any peripheral biological marker and the seizure quality as a surrogate for treatment efficacy has not been investigated so far. We prospectively examined serum brain-derived neurotrophic factor (BDNF) levels in 20 patients with major depression before and after electroconvulsive therapy. A seizure quality sum score for every ECT session was build up on the basis of the seizure duration, seizure amplitude, central inhibition, interhemispheric coherence and sympathetic activation. Serum BDNF levels were significantly higher after ECT (P = 0.036). In the linear regression analysis, a significant correlation of the serum BDNF levels and the time between the last ECT and the blood withdrawal (P = 0.01) was observed. The ANOVA revealed a significant influence of the interval between the last ECT and the blood withdrawal (P = 0.0017) as well as the seizure quality (P = 0.038) on the variance of BDNF serum levels. Our data corroborate the neurotrophin hypothesis suggesting an ECT-induced central BDNF rise leading to a delayed (>6 days) and increased equilibrium of the peripheral BDNF. The association of seizure adequacy with a BDNF rise might underline the importance of monitoring seizure quality markers in daily practice.